2015
DOI: 10.1111/pai.12319
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced bronchospasm diagnosis in children. Utility of combined lung function tests

Abstract: Methacholine and mannitol tests detect BHR in most children with suspected EIB. Bronchodilator and exercise tests show a low positivity rate. A combination of the methacholine test, followed by the mannitol test, gives the highest return to identify BHR in children for the diagnosis of EIB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 19 publications
6
6
0
Order By: Relevance
“…Overweight children were more than twice likely to report EL irrespectively of any other included factor. The 20% of children reporting EL is lower than the general activity limitation reported in 52% of children with current asthma (23), although the frequency of EIB (35%) among children reporting EL in the present study was comparable to previously reported range between 8 and 42% in studies comparing self-reported symptoms with EIB test (5,6,8,9,24). Nevertheless, 67 of 264 (25%) had a positive EIB compared to previously reported 51-55% (25,26) including also children with current asthma and ICS treatment.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Overweight children were more than twice likely to report EL irrespectively of any other included factor. The 20% of children reporting EL is lower than the general activity limitation reported in 52% of children with current asthma (23), although the frequency of EIB (35%) among children reporting EL in the present study was comparable to previously reported range between 8 and 42% in studies comparing self-reported symptoms with EIB test (5,6,8,9,24). Nevertheless, 67 of 264 (25%) had a positive EIB compared to previously reported 51-55% (25,26) including also children with current asthma and ICS treatment.…”
Section: Discussionsupporting
confidence: 69%
“…Despite no significant association between a positive EIB and perceived EL, the associations between R max %FEV 1 as well as severe BHR and EL suggest that perceived EL reflects BHR. This is supported by a report by Sanchez-Garcia et al (24), suggesting that the direct methacholine challenge and the indirect mannitol tests have high sensitivities to detect BHR in steroid-naive children complaining of one or more symptoms after exercise. Sanchez-Garcia et al (24) reported a detection rate of BHR in 96.7% with a methacholine test, increasing to 100% when combined with mannitol test (24).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Pediatric asthma is an enormous challenge for clinicians, not only for diagnosis but also in terms of prognosis and follow-up. [ 96 ] An inflammatory biomarker, giving additional information, would represent an immense benefit in daily clinical practice. However, at present, an optimal inflammometry biomarker does not exist.…”
Section: Discussionmentioning
confidence: 99%